Step-by-step explanation
To solve the given equation:
![-4=(v+6)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/awogghtj0urnk1dnq5422x1vucwi4q0n3r.png)
Step 1:
Multiply both-side of the equation by 2 in other to eliminate the denominator.
![-4*2=((v+6))/(2)*2](https://img.qammunity.org/2023/formulas/mathematics/college/mmftwbjo60kk8c5zac5s6heojlxw800kac.png)
At the right-hand side of the equation, 2 add the numerator will cancel-out 2 at the denominator.
![-8=\frac{(v+6)}{\cancel{2}}*\cancel{2}](https://img.qammunity.org/2023/formulas/mathematics/college/sgc1kt5hdkgoivpaievxl5olmuc3uu8pv3.png)
- 8 = v+ 6
step 2:
Subtract 6 from both-side of the equation.
That is;
-8 - 6 = v + 6 - 6
-14 = v
Hence, the value of v = -14